ANALISIS DAN PERANCANGAN SISTEM PENJUALAN PADA TOKO XYZ BERBASIS WEB DAN MOBILE MENGGUNAKAN UML - Budiman; Zatin Niqotaini; Ari Rizki Fauzi; Imannudin Akbar (NUANSA INFORMATIKA, 2023)
Technological advancements have a significant impact on businesses, particularly in the realm of sales. XYZ store currently relies on manual business processes, leading to a non-computerized and uncoordinated sales system. Consequently, there is a need for an innovative new business model that utilizes web and mobile-based systems. In this study, Rosa A.S.'s Prototype research method is employed to design the sales system using UML notation in the form of diagrams. The designed sales system caters to three user categories: customers accessing the mobile platform, store clerks, and store owners accessing the website platform. The study's outcomes consist of an analysis report and the design of a web- and mobile-based sales information system (mock-up) for XYZ store. The aim is to create a user-friendly interface that facilitates understanding for the sellers, making sales transactions more efficient. Moreover, the system aims to enhance convenience for customers and buyers, enabling them to conduct transactions and access product information from any location